NOTCH, ASCL1, p53 and RB alterations define an alternative pathway driving neuroendocrine and small cell lung carcinomas. Issue 4 (25th September 2015) - Meder, Lydia; König, Katharina; Ozretić, Luka; Schultheis, Anne M.; Ueckeroth, Frank; Ade, Carsten P.; Albus, Kerstin; Boehm, Diana; Rommerscheidt‐Fuss, Ursula; Florin, Alexandra; Buhl, Theresa; Hartmann, Wolfgang; et al.
Abstract : Small cell lung cancers (SCLCs) and extrapulmonary small cell cancers (SCCs) are very aggressive tumors arising de novo as primary small cell cancer with characteristic genetic lesions in RB1 and TP53 . Based on murine models, neuroendocrine stem cells of the terminal bronchioli have been postulated as the cellular origin of primary SCLC. However, both in lung and many other organs, combined small cell/non‐small cell tumors and secondary transitions from non‐small cell carcinomas upon cancer therapy to neuroendocrine and small cell tumors occur. We define features of "small cell‐ness" based on neuroendocrine markers, characteristic RB1 and TP53 mutations and small cell morphology. Furthermore, here we identify a pathway driving the pathogenesis of secondary SCLC involving inactivating NOTCH mutations, activation of the NOTCH target ASCL1 and canonical WNT‐signaling in the context of mutual bi‐allelic RB1 and TP53 lesions. Additionaly, we explored ASCL1 dependent RB inactivation by phosphorylation, which is reversible by CDK5 inhibition. We experimentally verify the NOTCH‐ASCL1‐RB‐p53 signaling axis in vitro and validate its activation by genetic alterations in vivo . We analyzed clinical tumor samples including SCLC, SCC and pulmonary large cell neuroendocrine carcinomas and adenocarcinomas using amplicon‐based Next Generation Sequencing, immunohistochemistry and fluorescence in situ hybridization. In conclusion, we identified a novel pathway underlying rare secondary SCLC which may drive small cell carcinomas in organs other than lung, as well. Abstract : What's new? Using next generation sequencing and establishing features of 'small cell‐ness', we identified a NOTCH‐ASCL1‐RB1‐TP53 signaling axis driving small cell cancers. In contrast to the previously described bi‐allelic RB1/TP53 loss in neuroendocrine stem cells as origin of primary small cell neuroendocrine cancers, the NOTCH‐ASCL1 mediated signaling defines an alternative pathway driving secondary small cell neuroendocrine cancers arising from non‐small cell cancers. Moreover, we show a preclinical rational for therapeutically testing WNT‐inhibitors in small cell cancers.